1982
DOI: 10.1136/bmj.284.6328.1529
|View full text |Cite
|
Sign up to set email alerts
|

Peritonitis associated with vaginal leakage of dialysis fluid in continuous ambulatory peritoneal dialysis.

Abstract: SHORT REPORTSPeritonitis associated with vaginal leakage of dialysis fluid in continuous ambulatory peritoneal dialysisAs the use of continuous ambulatory peritoneal dialysis for the treatment of end-stage renal failure increases so rarer complications of this treatment are being recognised.' We report a case of peritonitis with leakage of dialysis fluid from the peritoneum by way of the Fallopian tubes and uterus into the vagina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…The source of contamination in those cases not associated with catheter exit-site or tunnel infections is thought to be transmural [1,25]. Microorganisms can gain access to the peritoneum from the intestinal lumen or through genital organs [28,29]. Diagnostic instrumental procedures, such as colonoscopy, have been implicated in the development of these peritonitis episodes [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The source of contamination in those cases not associated with catheter exit-site or tunnel infections is thought to be transmural [1,25]. Microorganisms can gain access to the peritoneum from the intestinal lumen or through genital organs [28,29]. Diagnostic instrumental procedures, such as colonoscopy, have been implicated in the development of these peritonitis episodes [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic instrumental procedures, such as colonoscopy, have been implicated in the development of these peritonitis episodes [12,13]. However, in many cases there is no evidence that links peritonitis to colonoscopy as a risk factor [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Late leaks are most often related to a mechanical or surgical tear in the peritoneal membrane, occur beyond the first month of treatment, and usually present as internal leakage (pleural cavity, abdominal wall, external genitalia) (3,4). Multiple surgical operations, use of steroids, hypothyroidism, polycystic kidney disease, recurrent peritonitis, obesity, and high dialysate volume may cause abdominal wall weakness, hernias, and high intra-abdominal pressure and can be considered main predisposing factors for dialysate leaks (3,4,6). Dialysate leakage to other body spaces, such as retroperitoneal, pleural, and pericardial spaces, has been reported in children and more frequently in adults (4,(7)(8)(9).…”
Section: Vaginal Dialysate Leakage In a Child On Peritoneal Dialysismentioning
confidence: 99%
“…It has been suggested that antibiotic prophylaxis be given to immunocompromised patients and those with known valvular heart disease or prostheses prior to colonoscopy (4,5). Few cases have been reported in the literature on peritonitis following colonoscopy in CAPD patients (6)(7)(8)(9)(10). These reports suggested that diagnostic instrumental procedures such as colonoscopy may precipitate gram-negative peritonitis in CAPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Due to improvements in peritoneal dialysis technique and the enforcement of the aseptic precautions, there has been a reduction in peritonitis caused by gram-positive but not gram-negative organisms (11). The few case reports in the literature on peritonitis following colonoscopy were all in CAPD but not on APD patients (6,7,(12)(13)(14)(15). In the 2007 series reported by Yip et al (11), 3 of 5 peritonitis episodes were culture negative.…”
Section: Introductionmentioning
confidence: 99%